Evaluation of cryoablation using a prototype cryoablation needle in swine liver - Hyunjoon Son; Jonghyun Lee; Sung Yong Han; Tae In Kim; Dong Uk Kim; Daejin Kim; Gun-Ho Kim (Korean Society of Gastrointestinal Endoscopy, 2024)
Background/Aims Pancreatic cancer poses significant challenges due to its tendency for late-stage diagnosis and high mortality rates. Cryoablation, a technique used to treat various types of cancer, has shown potential in enhancing the prognosis of pancreatic cancer when combined with other therapies. However, its implementation is often limited by the need for lengthy procedures and specialized equipment. This study aims to develop a cryoablation needle optimized for endoscopic ultrasonography to simplify its application in treating pancreatic cancer. Methods The study involved conducting cryoablation experiments on swine liver tissue. It utilized cryo-needles to evaluate the extent of cell death across various temperatures and durations of cryoablation. Results The cryoablation system, which employed liquid carbon dioxide, achieved rapid cooling, reaching temperatures below -60 °C within 30 seconds and maintained the cryoablation process for 200 seconds. These conditions resulted in necrosis of the liver tissue. Notable cellular changes were observed up to 15 mm away from the cryoablation needle. Conclusions This experimental study successfully demonstrated the efficacy of using a cryo-needle for cryoablation in swine liver tissue. Further trials involving pancreatic tissue are expected to verify its effectiveness, underscoring the importance of continued research to establish its role as a complementary therapy in pancreatic cancer treatment.